Studi in onore di Angelo Monteverdi. Società Tipografica Editrice Modenese, Modena, 1959; 2 vols.: 924 pp. - Alatorre, Antonio; Frenk, Margit; Lope Blanch, Juan M. (El Colegio de México, 1962)
Se reseñó: Studi in onore di Angelo Monteverdi.